2020
DOI: 10.4028/www.scientific.net/kem.854.133
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Wear Resistance of Piston Rings of Internal Combustion Engines when Using Ion-Plasma Coatings

Abstract: Modern designs of piston rings of internal combustion engines and wear-resistant coatings used for them are considered. It is noted that the upper (compression) ring undergoes the most intense wear. Among the traditionally used wear-resistant coatings of compression rings, galvanic chrome plating and thermal spraying with molybdenum are most often used. The paper proposes the use of the ion-plasma spraying method for applying hard wear-resistant coatings to the working surface of piston rings based on titanium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, resistance tests of plates with and without nanocomposite coating showed that the application to the plates of hard alloy T15K6 coating based on Ti1-xAlxN, serviceability increased 3-4 times at cutting speeds of 3-4 m/s without the lubricating-cooling agent. In [11,12] it is showed the researches on increase of bearing wear resistance with the use of nanocomposite coatings. The paper [11] considers the application of nanocomposite coatings based on fluorocarbon composition on the parts working under fretting-corrosion conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, resistance tests of plates with and without nanocomposite coating showed that the application to the plates of hard alloy T15K6 coating based on Ti1-xAlxN, serviceability increased 3-4 times at cutting speeds of 3-4 m/s without the lubricating-cooling agent. In [11,12] it is showed the researches on increase of bearing wear resistance with the use of nanocomposite coatings. The paper [11] considers the application of nanocomposite coatings based on fluorocarbon composition on the parts working under fretting-corrosion conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The surface layer is structurally always heterogeneous. Also, the authors of many studies believe that the reduction of the roughness of the polished surface can be achieved by various methods, the choice or combination of which determines the success in solving the task [19][20][21][22][23]. But, unfortunately, the degree of influence of one or another technological factor on the roughness of the treated surface has not yet been clarified.…”
Section: Features Of Aluminum Alloy Processingmentioning
confidence: 99%
“…The magnetic field is necessary for the formation and retention of the magnetic abrasive brush at the working poles of the magnetic abrasive installation, the action of magnetic induction on the magnetic particles of the magnetic abrasive brush, due to which the tangential Ft and normal Fn forces acting on the abrasive particles are formed. When an abrasive particle held by magnetic particles comes into contact and presses against the surface of the workpiece due to the action of the normal force Fn, it scratches the surface of the workpiece due to the action of the tangential force Ft, producing material removal [22,25]. Thus, a qualitative surface layer of the part is formed.…”
Section: Features Of Aluminum Alloy Processingmentioning
confidence: 99%
“…Abrasion resistance was also shown to be stronger in the coated engine than in the uncoated engine. Titanium nitride and molybdenum nitride were considered as the most common representations of wear resistant coatings based on nitrides to increase the abrasion resistance of engine components [18]. Wear resistance and corrosion resistance are both improved by chromium carbide.…”
Section: Abrasion Resistancementioning
confidence: 99%